Lasik in Hyperopic Eyes with Congenital Nystagmus: A Case Report - Khabir Ahmad, Sharmeen Akram, Zarksis H. Anklesaria (Pakistan Journal of Ophthalmology, 2018)
Patients with nystagmus are considered to be poor candidates for laser in situ keratomileusis (LASIK), because they are unable to fixate. This case report presents the first reported use of LASIK surgery with a solid-state laser in hypermetropia and congenital nystagmus. A 23 year old woman with congenital nystagmus had LASIK surgery to correct a refractive error of +2.25/+1.75 90º in the right eye and + 2.00 / +1.75 90º in the left one. Baseline uncorrected visual acuity (UCVA) was 20/200 in both eyes, and best spectacle corrected visual acuity was 20/40 in both the eyes. The procedure was performed using the Nidek MK-2000 microkeratome and a CustomVis solid state laser system. Twenty four hours postoperatively, the patient had a UCVA of 20/50 in each eye which remained unchanged at 1 week and 8 weeks. Conclusion: LASIK surgery using solid state laser was effective in this case of congenital nystagmus. However, more cases should be examined before conclusions can be drawn.